2022
DOI: 10.1177/1071181322661449
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Peer Influence on Parent Willingness to Transport Children in Autonomous Vehicles

Abstract: When considering autonomous vehicles (AV) as a potential to increase the mobility of children, one must consider parent opinion, as parents make transportation decisions for their families. This decision making may be impacted by several factors including peer influence on technology adoption from other parents. The current paper examines the potential for the social influence of other parents to impact parent willingness to adopt AVs for their own teenagers. Early adopter status was found to be significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 18 publications
2
4
0
Order By: Relevance
“…In this case, trust referents came from family members, pop culture reporters, experience from their own vehicles and technologies in general, and social media. A similar mechanism of peer influence was observed with parents' willingness to let their children ride unattended in an AV (Ayala et al, 2022 ). Users are also anthropomorphized by conversing and relating their experience with other vehicles to their experience with the Tesla.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…In this case, trust referents came from family members, pop culture reporters, experience from their own vehicles and technologies in general, and social media. A similar mechanism of peer influence was observed with parents' willingness to let their children ride unattended in an AV (Ayala et al, 2022 ). Users are also anthropomorphized by conversing and relating their experience with other vehicles to their experience with the Tesla.…”
Section: Resultssupporting
confidence: 58%
“…AV (Ayala et al, 2022). Users are also anthropomorphized by conversing and relating their experience with other vehicles to their experience with the Tesla.…”
Section: Figurementioning
confidence: 99%
“…This factor has been considered as one of the main factors affecting individuals' intention to use AVs. A well-established positive relationship has been reported in prior research [9,[31][32][33][34], indicating that individuals with higher innovativeness are more likely to adopt autonomous mobility for their children's school travel mode. Perceived usefulness refers to how much a person believes that using a particular technology will be beneficial to them [38].…”
Section: Literature Reviewsupporting
confidence: 53%
“…Parents' gender is also another factor that has been considered in previous studies. In most prior studies, it has been concluded that fathers are more likely to allow their children to use autonomous mobility as a school travel mode [7,31,32,35]; however, no significant relation was found by Ayala et al [33] or Anania [36]. Parents' education level is another demographic factor that positively influenced their intentions to use AVs in most studies [9,31,32,34]; however, Mao et al [7] found no significant relationship between these two factors.…”
Section: Literature Reviewmentioning
confidence: 96%
See 1 more Smart Citation